1971
DOI: 10.1021/es60050a006
|View full text |Cite
|
Sign up to set email alerts
|

Copper-binding activity of tobacco smoke condensate

Abstract: The distribution of copper between a buffered aqueous solution of the metal ion and a n organic solution of tobacco smoke condensate (TSC) in 4-methyl-2-pentanone (MIBK) has been studied. The analytical parameters, metal ion and hydrogen ion concentrations, were investigated. Metal ion concentrations were determihed by atomic absorption spectrophotometry. TSC was collected with use of a Mason Mark I11 Smoker and acetone traps maintained at 0°C. This material was transferred to MIBK by evaporation at reduced pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The fractions obtained were tested with a biphasic extraction technique (Michael et al, 1971) for the ability of forming neutral complexes with Cu(II). A 10-ml volume of an aqueous solution of 0.01M CuCl2 in 0.1M tris at pH 5.7 was equilibrated with an equal volume of the mibk solution of each fraction obtained from the fractionation of five cigarettes equivalent of tsc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fractions obtained were tested with a biphasic extraction technique (Michael et al, 1971) for the ability of forming neutral complexes with Cu(II). A 10-ml volume of an aqueous solution of 0.01M CuCl2 in 0.1M tris at pH 5.7 was equilibrated with an equal volume of the mibk solution of each fraction obtained from the fractionation of five cigarettes equivalent of tsc.…”
Section: Resultsmentioning
confidence: 99%
“…A previous paper (Michael et al, 1971) reported the copper-binding activity of tobacco smoke condensate (tsc) by measuring copper chelates extractable in the organic phase in a two-phase system.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…), photosensitizing properties (photo-oxidation) (2), redox properties (dye-reducing, ascorbate oxidation) (J, 4). In addition other properties such as alkylating (.~) and metal-binding (6) properties have been reported. This paper describes yet another property of tobacco smoke, its antioxidant activity.…”
mentioning
confidence: 99%